Mining and quantitative evaluation of the laboratory biosafety policy in China - Cheng Xiang; Qing Zhu; Jinqing Wen; Lixiang Xie; Rongrong Hao; Xueting Qiu; Fei Zhu (PLoS ONE, 2025)
Policies play a pivotal role in guiding and overseeing laboratory biosafety management. To ensure that laboratory biosafety management is underpinned by scientifically robust and well-founded policies, an analysis and evaluation of existing policies were conducted. The object was to identify their merits and limitations, thereby offering references for future policy development. The qualitative and quantitative analysis were employed to explore 137 central-level policies issued in China as of April 30, 2024. Additionally, based on policy evaluation theory, a PMC index model was established to evaluate 11 representative laboratory biosafety policies. The results showed that: Firstly, these policies, promulgated by 24 distinct departments, spanned three regulatory tiers: laws, regulations, and administrative rules. Secondly, content analysis revealed three primary aspects: (1) management systems, (2) facility, equipment and containment barrier, and (3) operational technical standards. Thirdly, the average PMC index of the 11 policies was 5.05. Specifically, two policies were deemed excellent, eight policies were acceptable and one was inadequate. The low score was mainly attributed to three indicators: policy level, policy timeliness, and policy content. To sum up, laboratory biosafety policies in China were generally rational and comprehensive. However, insufficient collaboration among departments during policy formulation, as well as the need to improve policy continuity were identified. To enhance biosafety laboratory management, four recommendations are proposed: 1. Strengthen communication among different departments; 2.Optimize the policy formulation process; 3. Enhance supervision of biosafety level 1 and 2 (BSL-1/2) laboratories; 4. Harnessing the power of industry associations.